The System of Rating Investment Attractiveness of Businesses - Nataliya S. Plaskova; Lyudmila O. Petrushina (Учёт. Анализ. Аудит, 2019)
In the framework of designing the universal methodology of rating investment attractiveness of businesses the authors offer a solution to the problem of systematizing the modern approaches to assessing the investment attractiveness into conventional and modern ones. The paper focuses on drawbacks of existing methodology of investment analysis including the lack of strategic targeting in modern tools of rating investment attractiveness of businesses which prevents the management from reacting in timely and due manner to the dynamics of external impact beyond their control. The authors propose to use strategic economic analysis as a prospective method of rating investment attractiveness of businesses. The use of such a method makes it possible to decrease the risk of deviation from the strategic direction of business development providing the manager with a range of ready-made solutions and enhancing the credibility of potential investors.